Determinants of internationalization and performance of small and medium enterprises in Malaysia / Mohd Najib Bin Md Saad - Md Saad, Mohd Najib (2014)

(untitled)
The past two decades have seen a sharp increase in academic studies and public policy research concerned with the internationalization and performance of small and medium enterprises (SMEs). From this perspective, it is the influence of organizational and environmental characteristics on the internationalization process, as well as the effects of internationalization on firm performance, that have been the focus of scholars. Nevertheless, little is yet known of the internationalization determinants of SMEs in developing countries, and a lack of empirical evidence in the literature provides strong ground for this research. This study fills the void by documenting the relationships between organizational and environmental characteristics - specifically, entrepreneurial orientation, global mindset, network relationships and government support –internationalization, and firm performance. Notably, the study also distinguishes between the financial and non-financial performance of SMEs, which further adds to its significance. The specific objectives of the study were to: (1) investigate the effects of entrepreneurial orientation, global mindset, network relationships and government support on internationalization (2) analyze the effects of internationalization on firm performance and (3) examine the mediating effects of internationalization on the relationships between entrepreneurial orientation, global mindset, network relationships and government support, and firm performance. iv A quantitative survey methodology was applied using self-administered questionnaire to collect data from a sample of Malaysian SMEs involved in international business. The key informants were the owners or the highest ranking officers of the firms, who were the most knowledgeable about their firms’ characteristics, international operations and performance. The final 237 completed questionnaires yielded an effective response rate of 20 percent. Data collected were then analyzed using structural equation modeling to examine associative relationships among the three main constructs. The study has discovered several interesting findings which point to differences between international SMEs in developed and developing countries. First, contrary to earlier research in developed countries, current findings showed that entrepreneurial orientation, global mindset and network relationships were not positively related to internationalization. Second, a very strong positive relationship between government support and internationalization was observed here. Thus, unlike the situation in developed countries, government support has emerged as a more powerful determinant of internationalization than organizational characteristics among Malaysian SMEs. In addition, the results of this study have provided important empirical evidence for the positive effect of internationalization on both financial and non-financial performance of Malaysian SMEs. Internationalization also partially mediates the relationships between entrepreneurial orientation, global mindset, v network relationships and government support, and firm performance. Therefore, the current findings have emphasized internationalization as a key factor toward enhancing the performance of Malaysian SMEs. The study is expected to make a valuable contribution to knowledge of SME internationalization in developing countries, especially in the context that relates internationalization to organizational and environmental characteristics, and firm performance. It also has implications in the form of best practices for Malaysian SMEs. At the same time, it can provide directions for the government and policy-makers in their effort to develop policies and programs for the betterment of this particular business community